Debris flows and water tracks in northern Victoria Land, continental East Antarctica: a new terrestrial analogue site for gullies and recurrent slope lineae on Mars - Hauber, Ernst; Sassenroth, C.; de Vera, Jean Pierre Paul; Schmitz, Nicole; Jaumann, R.; Reiss, Dennis; Hiesinger, H.; Johnsson, Andreas (Geological Society, London, Special Publications, 2019)
Although the present environmental conditions on Mars prohibit the generation of significant volumes of liquid water, observations of several very young landforms, such as gullies and recurrent slope lineae, have been interpreted as signals for aqueous processes. To explore the range of conditions under which such features can be formed on Earth, a field site in northern Victoria Land, East Antarctica, was geomorphologically investigated. Despite the small size of the icefree area, the site displays gullies, water tracks and other traces of liquid water. The gullies show clear evidence of sediment transport by debris flows, and are typical of paraglacial processes on steep slopes in a recently deglaciated area. Water tracks appear in different forms, and seem to recur seasonally in the austral summer. Melting of snow and surface glacier ice is the major water source for both debris flows and water tracks. The observations presented here highlight the potential for hyperarid polar deserts to generate morphogenetically significant amounts of meltwater. The gullies are morphologically analogous to Martian gullies, and water tracks on steep slopes appear very similar to recurrent slope lineae. The observations suggest that even small icefree sites in continental Antarctica may enable observations which can serve as a basis for working hypotheses in Mars analogue studies, and future field work should consider more areas in Antarctica in addition to the McMurdo Dry Valleys to search for Mars analogue landforms.